Pengaruh Kejujuran Wajib Pajak, Kemauan Membayar Wajib Pajak Dan Kualitas Pelayanan Terhadap Penerimaan Pajak Pada Masa Pandemi Covid-19 Di KPP Pratama Medan Petisah - Purba, Rosanna; Hasibuan, Renika; Mei Hayani Ginting, Rika (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
This study aims to analyze the effect of taxpayer honesty, taxpayer willingness to pay, and service quality on tax revenue at the KPP Pratama Medan Petisah. Each of taxpayer honesty, taxpayer willingness to pay, and service quality will be tested and analyzed partially and simultaneously on tax revenue This study uses primary data. Samples were taken by incidental sampling technique, with a total sample of 98 respondents. The method of collecting data related to the research problem was carried out using the questionnaire method. The statistical model used is a multiple linear regression model by SPSS program. The conclusion of this study showed that partially the taxpayer honesty had an effect on tax revenue otherwise taxpayer willingness to pay and service quality had no effect on tax revenue at the KPP Pratama Medan Petisah. Based on the results of the simultaneous test that taxpayer honesty, taxpayer willingness to pay, and service quality together have a significant effect on tax revenue at the KPP Pratama Medan Petisah.